Group Decision Support System for Selecting Student Study Concentrations Using TOPSIS - Muhammad Baluqiah Al Ghazali; Indra Kanedi; Devi Sartika (Jurnal Media Computer Science, 2026)
The use of GDSS in concentration selection using TOPSIS method offers a systematic and data-driven approach to group decision-making. This enables more informed decisions that are widely accepted by all group members, thereby enhancing satisfaction and achieving better outcomes. This new system will be designed to be web-based using PHP and MySQL with computerized programs. Based on the results of the design, implementation, and testing of Group Decision Support System (GDSS) for selecting student concentrations using TOPSIS method, the following conclusions can be drawn: 1.GDSS system that was developed successfully helped the process of selecting student study concentrations objectively and efficiently. By considering various criteria (academic grades, student interests, lecturer recommendations, job opportunities, facilities), the system was able to recommend the right concentration choices. 2.TOPSIS method proved to be effective in calculating concentration alternatives based on the principle of distance from positive and negative ideal solutions. 3.The use of the system accelerates the decision-making process. The average time required to determine a concentration has decreased drastically from approximately 1–2 days (manually) to less than 20 minutes with the system's assistance. 4.The implementation of a web-based GDSS makes the system more flexible and easily accessible to all parties involved, including faculty, students, and administrators